Nepali Art: Thoughts & Musings by Madan Chitrakar Review - Sharma, Yam Prasad (SIRJANĀ – A Journal Of Arts and Art Education, 2022)
Madan Chitrakar's Nepali Art: Thoughts & Musings presents a mosaic of Nepali art including research articles on Nepali paintings, sculptures and architecture. He has traced the native cultural roots and myths in the artworks including the connection of tradition and modernity. Thematic undercurrents along with stylistic innovation have been presented in flowing language of the veteran art writer and critic. The work points out the different dimensions of Nepali aesthetics. The essays are representative of certain genres, forms and issues. To have the view of holistic picture of Nepal art, more explorations in the uncovered issues are expected from the author.